Distorsi Perilaku Keberagamaan Masyarakat Majemuk dalam Membangun Toleransi Beragama di Dukuh Kayuapu - Dewi, Siti Malaiha; Hidayah, Novi Nurul (Prodi Aqidah dan Filsafat Islam, Fakultas Ushuluddin, Universitas Islam Negeri Sunan Kudus, 2017)
The application of inter-religious tolerance in Kayuapu has been distorted. This research is a qualitative field research. Sources of the data were collected from observations or documentation and interviews with Muslim and Christian communities in the Kayuapu Kulon, Kudus Regency, Central Java, Indonesia. The result is revealed that the tolerance understood by the Kayuapu community are provides freedom for anyone to embrace religion and the practice of worship according to their own beliefs. But some residents also practice religious conversion repeatedly. The contributing factors are: first, environmental factors or playmates; second, changes in status such as marriage and divorce; third, economic factors (poverty); and fourth, the lack of understanding of religion.